Automated Operant Conditioning in the Mouse Home Cage - Francis, Nikolas A.; Kanold, Patrick O. (Frontiers in Neural Circuits, 2017)
Recent advances in neuroimaging and genetics have made mice an advantageous animal model for studying the neurophysiology of sensation, cognition and locomotion. A key benefit of mice is that they provide a large population of test subjects for behavioral screening. Reflex-based assays of hearing in mice, such as the widely used acoustic startle response, are less accurate than operant conditioning in measuring auditory processing. To date, however, there are few cost-effective options for scalable operant conditioning systems. Here, we describe a new system for automated operant conditioning, the Psibox. It is assembled from low cost parts, designed to fit within typical commercial wire-top cages, and allows large numbers of mice to train independently in their home cages on positive reinforcement tasks. We found that groups of mice trained together learned to accurately detect sounds within 7-10 days of training. In addition, individual mice isolated from groups also showed good task performance. The Psibox facilitates high-throughput testing of sensory, motor and cognitive skills in mice, and provides a readily available animal population for studies ranging from experience-dependent neural plasticity to rodent models of mental disorders.